A Political Disconnect? Evidence from Voting on EU Trade Agreements - Paola Conconi; Florin Cucu; Federico Gallina; Mattia Nardotto (CESifo GmbH, 2024)
The European Union (EU) has long been accused of suffering from a "democratic deficit." The European Parliament (EP), the only EU institution directly elected by citizens, is seen as having limited powers. Moreover, its members (MEPs) are often portrayed as unresponsive to the interests of their constituents due to the second-order nature of European elections: instead of being shaped by EU policies, they are driven by domestic politics. In this paper, we provide evidence against these Eurosceptic arguments using data on a key policy choice made by MEPs: the approval of free trade agreements. First, we show that MEPs are responsive to the trade policy interests of their electorate, a result that is robust to controlling for a rich set of controls, fixed effects, and employing an instrumental variable strategy. Second, we carry out counterfactual exercises demonstrating that the EP's power to reject trade deals can help explain why only agreements with broad political support reach the floor. Finally, against the idea that European elections are driven solely by domestic politics, we find that the degree of congruence between MEPs' trade votes and their electorate's interests affects their re-election chances.
Keywords: F13; D72; 330; EU democratic deficit; European Parliament; roll-call votes; trade agreements